2011
DOI: 10.1007/s10856-011-4430-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transient proanthocyanidins preconditioning on the cross-linking and mechanical properties of demineralized dentin

Abstract: Proanthocyanidin-based preconditioners were prepared by adding powdered proanthocyanidins-rich grape seed extract to various solvents at different concentrations. Demineralized dentin specimens were preconditioned for 20, 30, 60 or 120 s, followed by the evaluation of their cross-linking degree, mechanical properties and micromorphology. The cross-linking degree of the demineralized dentin collagen exhibited concentration- and time- dependent increase after preconditioning treatment, irrespective of the precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 33 publications
2
32
0
3
Order By: Relevance
“…Ninhydrin assay: The specimens were also subjected to a modified ninhydrin assay based on the previous report [26,27]. Briefly, ninhydrin was dissolved in PBS (0.3M, pH 7.4) with 0.3% fructose, specimens were heated with ninfydrin solution at 85℃ for 20min, 45% alcohol was added to the reaction system and the optical absorbance was recorded with a Multifunctional Microplate Reader (TECAN infinite M200 PRO, Austria) at 570nm.…”
Section: Loss Rate and Cross-linking Degree Detectionmentioning
confidence: 99%
“…Ninhydrin assay: The specimens were also subjected to a modified ninhydrin assay based on the previous report [26,27]. Briefly, ninhydrin was dissolved in PBS (0.3M, pH 7.4) with 0.3% fructose, specimens were heated with ninfydrin solution at 85℃ for 20min, 45% alcohol was added to the reaction system and the optical absorbance was recorded with a Multifunctional Microplate Reader (TECAN infinite M200 PRO, Austria) at 570nm.…”
Section: Loss Rate and Cross-linking Degree Detectionmentioning
confidence: 99%
“…It was found that collagen cross-linking treatment by PA-based preconditioners in a clinically applicable duration increased the cross-linking degree and ultimate tensile strength of demineralised dentin. 21 Therefore the aim of this study was to evaluate whether transient PA preconditioning can also improve dentin bonding characteristics, and whether the type of solvent, concentration of PA and the exposure duration will have influence on resin-dentin bonds. The null hypothesis tested was that the transient use of PA would not significantly affect resin-dentin bonds when compared to a non-treated group, regardless of the type of solvent, concentration and the exposure duration.…”
Section: Introductionmentioning
confidence: 99%
“…When PA interacts with collagen, it is capable of inducing inter-and intra-fibrillar, as well as inter-microfibrillar cross-links in the collagen matrix [43,53,54]. Numerous free phenyl hydroxyl groups are present in PA [55] which can create bridge-type hydrogen bonds with the side chains of hydroxyl, carboxyl, amino or amide groups of the collagen molecules [56,57].…”
Section: Discussionmentioning
confidence: 99%